Aerobic treatment of winery wastewater with the aim of water reuse - Oliveira, M. (2009)
An air micro-bubble bioreactor (AMBB) using a free self-adapted microbial population, 15dm3 working volume, was used for aerobic treatment of winery wastewater. This reactor utilizes a Venturi injector in conjunction with mass transfer multiplier nozzles, which allow an efficient oxygen transfer. The reactor can operate in batch or continuous conditions. The dynamics of chemical oxygen demand (COD), biomass and total contents of polyphenolic compounds was followed throughout each trial. The wastewater COD ranged between 4.0–8.0 kgCODm23 and the efficiency of the batch treatment was about 90.0 ^ 4.3%, after 6 days of operation. The maximum efficiency obtained was achieved after 15 days of treatment (99%). In continuous conditions, the loading rate and the treatment efficiency ranged between 0.45–1.00 kgCODm23 d21 and 93.3 ^ 2.0%, respectively. The AMBB hydraulic retention time was 15 days. To assess the suitability of treated water in relation to vineyard irrigation, the effluent was physico-chemical analysed and direct toxicity bioassays with effluent matrix were carried out using Lepidium sativum L. seeds. The results showed the water quality required to be reutilised minimizing water consumption. This study will contribute for the implementation of an efficient water use plan, aiming the preservation of the water resource and the reduction of the wastewater production